124k views
2 votes
Apply the Distributive Property to rewrite 2(6 - x) = 3. Then solve th equation Apply the Distributive Property to rewrite 2(6 - x)= 3. Choose the correct answer below, A. 6(2) – 6X = 3 OB. 2(6) - 2x = 3 OC. 6(2) +GX = 3 ED. 2(6) + 2x = 3​

2 Answers

6 votes

Answer:

x = ⁹⁄₂ Or 4.5

Step-by-step explanation:

2(6 - x) = 3

  • Apply Distributive Property

2(6 - x) = 3

  • 2(6) = 12, 2(x) = 2x
  • 12 - 2x = 3

12 - 2x = 3

  • Subtract 12 From Both Sides

12 - 2x - 12 = 3 - 12

  • Simplify

-2x = -9

  • Divide Both Sides By -2

-2x / -2 = -9 / -2

  • Simplify

x = ⁹⁄₂ Or 4.5

User Uri Abramson
by
5.3k points
14 votes

Answer:

Step-by-step explanation:

C

User WiseOldDuck
by
5.3k points